2016
DOI: 10.1002/2015je004864
|View full text |Cite
|
Sign up to set email alerts
|

Young Martian crater Gratteri and its secondary craters

Abstract: In response to questions that have been raised about formation and effects of secondary craters on crater chronometry techniques, we studied properties of the secondary crater field around the young Martian primary ray crater Gratteri (diameter 7 km). The crater has an estimated age of 1 to 20 Myr, based on counts of small craters on flat interior surface, consistent with a likely age for a young crater its size (Hartmann et al., 2010). The following are among our findings: (1) We identify an unusual class of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 64 publications
(170 reference statements)
1
26
0
Order By: Relevance
“…It cannot be ruled out that the rollover in the SFD of secondaries may be partly caused by the rollover in the fragment SFD at certain diameters [ Quantin et al ., ]. However, the geological context of the distant secondaries shown in Figures b and e suggests that substantial mutual destruction and interruption had occurred when the secondaries were formed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It cannot be ruled out that the rollover in the SFD of secondaries may be partly caused by the rollover in the fragment SFD at certain diameters [ Quantin et al ., ]. However, the geological context of the distant secondaries shown in Figures b and e suggests that substantial mutual destruction and interruption had occurred when the secondaries were formed.…”
Section: Resultsmentioning
confidence: 99%
“…However, interpretations about the dominance of background secondaries in small crater populations have been different, e.g., Dundas and McEwen [] versus Quantin et al . [].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schultz and Gault [] identified this as a feature of clustered subsonic laboratory impacts and suggested that it could be used to recognize distal secondaries. Numerous asymmetric ejecta secondaries were identified by Calef et al [] (from many of the same primaries as addressed in the present study) and Quantin et al [] (from Gratteri crater). Highly asymmetric ejecta blankets can form even for moderately oblique low‐velocity impacts (see Moore [, Figure 2], impact angle 45°).…”
Section: Methodsmentioning
confidence: 99%
“…Significant attention has focused on the size and spatial distribution of secondary craters to understand how these influence the chronology based on crater counting statistics [ Bierhaus et al , ; McEwen et al , ; McEwen and Bierhaus , ; Dundas and McEwen , ; Hirata and Nakamura , ; Werner et al , ; Xiao and Strom , ; Xiao , ]. Some of this work has involved detailed mapping of the secondary crater fields of large primary craters [ Preblich et al , ; Robbins and Hynek , , ; Chuang et al , ; Quantin et al , ]. The challenge of identifying relatively recent secondary craters was helped by the work of Tornabene et al [, ], which described features common to well‐preserved complex primaries on Mars.…”
Section: Introductionmentioning
confidence: 99%